Deficit Irrigation Strategies in Vitis vinifera L. cv. Cannonau under Mediterranean Climate. Part II - Cluster Microclimate and Anthocyanin Accumulation Patterns - Fernandes de Oliveira, A.; Nieddu, G. (South African Journal of Enology and Viticulture, 2016)
The contribution of light and thermal conditions to berry anthocyanin accumulation was investigated in grapevine Vitis vinifera L. cv. Cannonau/1103P subjected to different irrigation strategies in Sardinia, Italy in 2009. In two of the deficit irrigation treatments the root system received 50% and 25% crop evapotranspiration (ETc), referred to as DI50 and DI25, respectively. In the third treatment, which included partial root-zone drying (PRD), ETc was set at 50%. All three treatments were compared to a full irrigation control (FI), thus 100% ETc. Analysis of the thermal conditions during the growing season in 2009 provided evidence for a high frequency of elevated temperatures (> 30°C) during berry development. During ripening, the DI25 clusters intercepted significantly higher intensities (P < 0.01) of solar radiation, UV and PAR, particularly on the southeast canopy side, in comparison to FI and PRD. The analysis of berry temperatures in the DI treatments showed higher exposure to more than 35°C in the DI25 southeast berries. Thermal time for anthocyanin accumulation was computed for the DI50 and DI25 berries using normal heat hours (NHH). The patterns of daily NHH showed a reduction in thermal efficiency for anthocyanin accumulation during mid-ripening in the DI25 southeast berries compared to the DI50 ones. The higher temperatures at mid-ripening led to lower total anthocyanin contents in the DI25 berries. However, the coumaroyl-glucoside anthocyanin forms continued to increase in both the DI50 and DI25 berries, while a significant reduction in berry total contents of these forms was observed in FI and PRD. Both deficit irrigation and light conditions in the DI25 berries favoured the accumulation of more colourstable anthocyanins in the berry skin until harvest, namely p-coumaroyl-glucoside and acetyl-glucoside forms.